Unrecognised pheochromocytoma in pregnancy discovered through metoclopramide-triggered hypertensive emergency - Aurelio Negro; Ignazio Verzicco; Stefano Tedeschi; Rosaria Santi; Barbara Palladini; Anna Calvi; Alessandro Giunta; Davide Cunzi; Pietro Coghi; Riccardo Volpi; Aderville Cabassi (Blood Pressure, 2021)
Purpose Pheochromocytoma, a catecholamine-secreting tumour leading to neurological and cardiovascular life-threatening conditions through hypertension crisis, occurs in 0.1-0.5% of hypertensive patients, but it is extremely rare in pregnancy (0.0018-0.006%). Some classes of drugs, even commonly used in pregnancy, can trigger catecholamine secretion, precipitating the clinical situation. Materials and Methods and Results We report a 33-year-old woman, gravida 2 para 1, with previous mild hypertension, was admitted to the emergency room, at 28 2/7 weeks of gestation due to headache, tachycardia and severe arterial hypertension (220/120 mm Hg) triggered by the antiemetic metoclopramide used for a week because of nausea. In the emergency room, a paradoxical rise in blood pressure followed intravenous labetalol infusion was observed. Both metoclopramide and labetalol-triggered hypertensive crisis raised the suspicion of an undiagnosed pheochromocytoma. Diagnostic work-up showed elevated normetanephrine urinary excretion ​​and a right adrenal pheochromocytoma by abdominal magnetic resonance imaging. Oral alpha-1 and beta-1-adrenergic antagonist and calcium-channel blocker were started. At 33-weeks of gestation, she underwent a caesarean section giving birth to a female child. Seven weeks later she underwent a video-laparoscopic right adrenalectomy which normalised her blood pressure. Conclusions Both metoclopramide, a selective dopamine type-2 receptor antagonist and partial agonist of 5-hydroxytryptamine 4 receptor, and labetalol, a non-selective β-adrenoreceptor-blocker with weak α1-adrenergic antagonism, exacerbated an acute hypertensive crisis revealing an unrecognised pheochromocytoma in a pregnant patient. Careful attention to potential drug-triggered catecholamine crises and especially early recognition of pheochromocytomas, are mandatory in hypertensive pregnant women. A missed or delayed diagnosis could result in catastrophic results affecting foetal and maternal outcomes.